ANALISA LAPORAN KEUANGAN DENGAN MENGGUNAKAN METODE DU-PONT SYSTEM - Saparliddin; Stefanie Polopodang; Ade Bagus (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
The financial report is a record of the company's financial information in an accounting period that describes the condition or performance of the company. Analysis of financial statements can use the du-pont system, analysis of the Du-Pont system is an analysis system that is intended to show Net Profit Margin (NPM), Total Assets Turnover (TATO), and Return On Investment (ROI) interact with each other to determine Return On Equity (ROE). This type of research is descriptive research with a quantitative approach. The data in this study are secondary data derived from annual financial reports which are calculated and analyzed using the du-pont system method and then the results are interpreted. The results showed that the net profit margin, total asset turnover, equity multiplyer and return on investment increased and decreased every year so that the return on equity also fluctuated but was not too significant.